The Route of Sucrose Utilization by Streptococcus mutans Affects Intracellular Polysaccharide Metabolism - Costa Oliveira, Bárbara Emanoele; Ricomini Filho, Antônio Pedro; Burne, Robert A.; Zeng, Lin (Frontiers in Microbiology, 2021)
Streptococcus mutans converts extracellular sucrose into exopolysaccharides (EPS) by glucosyl- and fructosyl-transferase enzymes and internalizes sucrose for fermentation through the phosphotransferase system (PTS). Here, we examined how altering the routes for sucrose utilization impacts intracellular polysaccharide (IPS; glycogen) metabolism during carbohydrate starvation. Strain UA159 (WT), a mutant lacking all exoenzymes for sucrose utilization (MMZ952), and a CcpA-deficient mutant (∆ccpA) were cultured with sucrose or a combination of glucose and fructose, followed by carbohydrate starvation. At baseline (0 h), and after 4 and 24 hours of starvation, cells were evaluated for mRNA levels of the glg operon, IPS storage, glucose-1-phosphate (G1P) concentrations, viability, and PTS activities. A pH drop assay was performed in the absence of carbohydrates at the baseline to measure acid production. We observed glg operon activation in response to starvation (p <0.05) in all strains, however such activation was significantly delayed and reduced in magnitude when EPS synthesis was involved (p <0.05). Enhanced acidification and greater G1P concentrations were observed in the sucrose-treated group, but mostly in strains capable of producing EPS (p <0.05). Importantly, only the WT exposed to sucrose was able to synthesize IPS during starvation. Contrary to CcpA-proficient strains, IPS was progressively degraded during starvation in ∆ccpA, which also showed increased glg operon expression and greater PTS activities at baseline. Therefore, sucrose metabolism by secreted enzymes affects the capacity of S. mutans in synthesizing IPS and converting it into organic acids, without necessarily inducing greater expression of the glg operon.